Pengaruh Pengendalian Internal dan Audit Internal Terhadap Kinerja Penjualan Perusahaan (Studi Pada PT B&K Baja Utama - Ratu Agi Anandi Tatiana; Haryono Umar (Sekolah Pascasarjana Perbanas Jakarta, 2018)
Companies need a system to detect any problems. one of the systems that support and to note is the existence of an internal control in our operations PT B&K Baja Utama which require the existence of internal audit as a supervisor in the PT B&K Baja Utama to achieve its objectives. The purpose of this study was to determine the effect of internal control and internal audit of the performance of sales. The method used is the approach through case studies, which examined one of the problems that exist in the company, whereas the method used is quantitative method. Data collection techniques were studied in the form of primary data collection techniques were done in two ways, namely questionnaires and case studies. The results of this research have indicated that the internal control significant effect on sales performance, internal audit significant effect on sales performance. Internal controls and internal audits have an effect on sales performance as it impacts sales growth